ANALISIS PENDAPATAN DAN PROSPEK AGRIBISNIS ABALON (HALIOTIS ASININA) DI KABUPATEN KONAWE DAN KOTA KENDARI - Rahmat Arif Adimulya; Onu La Ola; Azhar Bafadal (Universitas Halu Oleo, 2016)
Abalone (Haliotis asinina) is one of the economically valuable commodities of fishery. Abalon products have a high prices and market demand especially to export. This condition, abalone businesses should get a high income for them. The research was to analyze the abalone business doer in each level and developing prospect of abalone agribusiness in Southeast Sulawesi based on the relationship between agribusiness sub-system and the income gained. Respondents and population of research was the whole abalone business comprised of fishermen, cultivator, collector venders, and inter venders. Descriptive analysis is used to find out the relationship of abalone agribusiness sub-system, while income analysis is used to find out the income of abalone agribusiness. To see the prospect of abalone agribusiness the analysis of descriptive and income is used. Result of the research shown that the relationship of abalone agribusiness has not well integrated. The income gained by fishermen per season is Rp.309.211,- , and the collector vender is Rp.9.830.734,-, while the income of inter vender of province is Rp.12.282.976,-. From the result of the analysis can be concluded that abalone agribusiness has an average prospect to be developed in Konawe Regency.Keywords: abalone, agribusiness, income analysis, prospect of abalone